Consumer cooperatives : (World bank, 2006)
This paper describes the essential characteristics of consumer cooperatives engaged in the provision of basic services and discusses their applicability as a model for water supply and sanitation service provision in urban areas. A cooperative is an autonomous association of persons united voluntarily to meet their common economic, social, and cultural needs and aspirations through a jointly-owned and democratically-controlled enterprise. The paper focuses on system-wide urban water supply cooperatives and it is thus not concerned with urban or peri-urban cooperatives that depend on either boreholes or bulk purchases of water from a utility for distribution, nor does it refer to rural water supply cooperatives that are generally small.